Education and vulnerability strategies of coffee farmers in facing the climate change in Kekuyang Village, Aceh Tengah District [Edukasi dan strategi kerentanan petani kopi dalam menghadapi perubahan iklim di Gampong Kekuyang Kabupaten Aceh Tengah] - Fachruddin, Fachruddin; Pramulya, Rahmad; Ariska, Nana; Aulia, Muhammad Reza; Dahlan, Dahlan (Buletin Pengabdian, 2025)
Upas fungal disease on coffee plants is a threat that causes young plants to die. Poor access to infrastructure, especially roads to coffee farms for women farmers, as well as a lack of training on Good Agricultural Practices (GAP) and coffee agritourism, are also significant obstacles to the economic development of coffee farmers. In addition, population growth and new land clearing in unauthorized areas further worsen environmental and coffee land conditions in Kekuyang Village. This service aims to educate and strategize the vulnerability of coffee farmers in facing climate change in Kekuyang Village, Aceh Tengah District. The coffee farmer vulnerability education program has been implemented successfully through Focus group discussion (FGD). The team delivered educational materials focused on the application of adaptation strategies with a multidimensional approach. In the human aspect, training and raising awareness of sustainable agricultural practices are required. In the social dimension, strengthening community networks and cooperation with various parties is very important. Meanwhile, in the environmental aspect, crop diversification and the use of coffee varieties that are more resistant to climate change can help minimize risks. From a financial perspective, better access to insurance and value-enhancing products is a priority. In addition, improvements to agricultural infrastructure and the application of environmentally friendly technologies are key strategies to deal with the challenges of climate change in an integrated manner.